127 Equine Nutraceuticals: Is Science Finally Catching up to Fiction?. (8th October 2021) - Pearson, Wendy
Abstract: Nutraceutical supplements have become requisite fare in equine stables across North America and Europe, and a robust marketing engine has propagated the notion that every horse owner has the ability to contribute to the management – and even treatment – of some of the most important health and performance issues facing the modern horse. The voracious appetite of horse owners and managers for these supplements has vastly outpaced research into equine-specific efficacy, safety or toxicity of the majority of available products. Indeed, even government regulators have been left scrambling to accommodate the unique characteristics of nutraceuticals for horses within existing feed and drug guidelines, whilst the groundswell of consumer demand creates a fertile and attractive venue for a myriad of equine nutraceutical products. This presentation will identify peculiarities of horses and horse enthusiasts which define the opportunities and challenges associated with equine nutraceutical products. The current state of scientific inquiry will be explored, focusing on supplements targeting common equine health issues including arthritis, laminitis and gastrointestinal disorders. This critical mass of scientific evidence is then compared with popular marketing of equine nutraceuticals, in order to caliper the distance between science and fiction.